2004
DOI: 10.1159/000076345
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphism in Indian Patients with Alzheimer’s Disease and Vascular Dementia

Abstract: The association of apolipoprotein E (ApoE) gene polymorphism with Alzheimer’s disease (AD) has been reported in several populations including one from a rural community in North India. However, the association of ApoE polymorphism with vascular dementia (VaD) is yet to be established in this population. In a case-control study involving 54 cases of dementia (29 AD and 25 VaD) and 76 age-matched healthy controls, the frequency of Ε4 allele was significantly higher among cases of AD and VaD compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
25
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
9
25
2
Order By: Relevance
“…Such an observation has been well established in earlier reported studies as well. Among the genotypes, ε3ε4 was observed to be widely prevalent among the diseased groups in comparison to the healthy controls (p < 0.001), which is in accordance with earlier studies [36]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such an observation has been well established in earlier reported studies as well. Among the genotypes, ε3ε4 was observed to be widely prevalent among the diseased groups in comparison to the healthy controls (p < 0.001), which is in accordance with earlier studies [36]. …”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the frequency of the ε4 allele was significantly higher in cases of VaD patients (17.4%) in comparison to the control group (p = 0.003). The percentage prevalence of the ε4 allele was similar to studies from Hungary and China [11,33]; however, one of the previous studies from our institute reported a relatively higher frequency of the ε4 allele in VaD patients [36]. The discrepancy could perhaps be due to the difference in samplings and/or relatively lower sample size.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The ApoE4 allele was initially identified as a ‘risk factor’ for Alzheimer’s disease (AD), and later with other types of dementias like vascular dementia (VaD) [2] and frontotemporal dementia (FTD) [3]. ApoE4 is also a ‘risk factor’ for other age- and lifestyle-related conditions like diabetes [4], atherosclerosis, hyperlipidemia and cardiovascular conditions [2], which in turn are risk factors for neurodegeneration. Thus, the ApoE4 allele seems to increase the risk for AD and VaD, both directly and indirectly through other risk factors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Though the ApoE4 frequency and dementia is lower in India in comparison to Western populations, the positive association of ApoE4 is confirmed in epidemiologic- and clinic-based samples [2,7]. There is published work from northern India on ApoE gene polymorphism and dementia [2,7,9,10], but there is no published work on this aspect from southern India [11]. ApoE polymorphism in dementia from a hospital setting in Bangalore (southern India) is reported here.…”
Section: Introductionmentioning
confidence: 99%